Year-End Closing Strategy Assessment and Employee Performance Assessment in Food and Beverage Industry Companies - Nurul Fatwa Hasan (Smart International Management Journal, 2025)
The food and beverage industry faces intense competition and operational complexity, particularly during year-end closing periods. This study examines the impact of year-end closing strategies and employee performance evaluation on operational efficiency and financial performance. A mixed methods approach was applied, combining quantitative surveys of managers and employees, qualitative in-depth interviews, and secondary financial data analysis. Quantitative data were analyzed using descriptive statistics and regression analysis, while qualitative data were processed through thematic coding. The results indicate that effective year-end closing strategies significantly improve operational efficiency, employee productivity, and achievement of business targets. The integration of closing strategies and performance evaluation also has a positive impact on financial performance, reflected by an average return on investment (ROI) of 12.3%. Best practices identified include interdepartmental coordination, technology utilization, and continuous performance monitoring. However, challenges such as reliance on manual systems and inconsistent appraisal standards remain. This study provides empirical evidence that aligning strategic management and human resource management enhances sustainability and competitiveness in the food and beverage industry.